The Effect of Expiry time and Soaking Duration in Coconut Water on Watermelon Seed Invigoration (Citurullus lunatus Thunb. Matsum. et Nankai) - Boy Riza Juanda; Cut Mulyani; sofiyana sofiyana (Jurnal Penelitian Agrosamudra, 2017)
This research aims to determine the effect of expiry time and soaking duration in coconut water on watermelon seed invigoration and the interaction of the two treatments to invigorate watermelon seed. The results showed that the expiration treatment had a very significant effect on the observation parameter of sprout height but did not significantly affect other parameters. The best treatment was found on the 1 month expiration M1. The soaking of duration treatment in coconut water ZPT had a significant effect on growth potential, germination, growth rate, vigor index but no significant effect on the height of sprout and root length. The best treatment was found at a concentration of 250 cc / liter of water. The interaction of the two treatments had no significant effect on all observed parameters observed. Based on the results of the research, the seeds of expired watermelon can still be increased germination provided that expiry time used does not exceed 1 month, other than that the soaking of duration in coconut water as much as 250 cc / liter of water done separately can also increase the germination of expired watermelon.